Management accounting information system and intellectual capital: a way to increase SME’s business performance - Hariyati Hariyati; Dian Anita Nuswantara; Rendra Arief Hidayat; Insyirah Putikadea (Jurnal Siasat Bisnis, 2023)
Purpose – The paper aims to clarify the unclear relationship between management accounting information systems and SME business performance by having intellectual capital as mediating variable. This will expand the domain of management accounting information usage from SME’s perspective. Design/methodology/approach – The paper used a descriptive study using the close-ended questionnaire distributed to 428 SMEs in East Java Region. The data were complemented by statistical analysis using SMART PLS to test the mediation role of intellectual capital. Findings – The paper provided empirical evidence that intellectual capital plays as a quasi mediating for management accounting information system and business performance relationship. This encouraged SME to optimize their IT usage to maximize the benefit of implementing MAIS. Research limitations/implications – Since management accounting system needs for business varied, future study needs to consider the level of IT usage. Therefore, future researchers are encouraged to investigate how to set the usage level. Practical implications – The paper included implications for the development of higher level of IT usage, such as management accounting information system to gain the benefits, that is increased business performance. Originality value – This paper filled the gap in IT usage from SMEs’ perspective by expanding the role of intellectual capital on the relationship of management accounting information systems on business performance.